Chronic myelogenous leukemia occurring in two brothers: The opposite sides of the same coin?. (2021) - Verrou, Evgenia; Tsirou, Kyriaki; Karampatzakis, Nikolaos; Triantafyllou, Theodora; Sevastoudi, Aggeliki; Grigoriadou, Georgia I.; Konstantinidou, Pavlina; Panagiotidis, Panagiotis; Katodritou, Eirini
Abstract: Herein we present a rare case of two brothers diagnosed with CML four years apart. Importantly, our case of CML occurrence among siblings is the fifth one reported and the second one investigated by both, conventional cytogenetics and RT-PCR analysis. Moreover, although Ph chromosome was detected in both our patients, RT-PCR revealed the presence of two different BCR-ABL transcripts. Finally, both our patients have been followed for a long period of time offering thus the opportunity to observe the differences in the clinical course.